بلاغة الصورة الكاريكاتورية دراسة مقارنة للنص المصاحب باللغتين العربية والفرنسية - بوعزيز, العيد (كلية الأدب العربي والفنون, 2024)
نظرا للأهمية التي اكتسبها الكاريكاتير منذ ظهوره إلي يومنا هذا ،لما يؤديه من رسالة وما يخلفه من اثر في المتلقي، وعلى الرغم من اختلاف اللغة التي تصحب الصورة الكاريكاتورية أو حتى من دونها ، فانه يبقى ذلك الناطق الصامت كما يقولون ينتزع الفكرة وينقلها في يسر وسهولة إلى شريحة عريضة من المجتمع ،مستخدما بذلك مختلف الأسرار البلاغية التي لا تقل أهمية عن بلاغة الكلمة، خاصة انه قد استحوذ على فئات مختلفة من الجماهير ، لاسيما جمهور القراء. وفي بحثنا هذا أردنا أن نسلط الضوء على هذا الفن من خلال إجراء مقارنة للنص المصاحب (الرسالة الألسنية) للصورة الكاريكاتورية ، علنا نفيد بذلك المتلقي واستغلال الكاريكاتير في الحياة بما يخدم جوانبها المختلفة (التعليم، الإشهار ،السياحة...). Due to the importance acquired by the caricature since its appearance until today, for its interpretation of the message and the impact it leaves on the recipient, and despite the different language that accompanies the caricature image or even without her. It remains that the silent speaker, as they say, grasps the idea and easily and easily transfers it to a wide segment of society, using various rhetorical secrets that are no less important than the eloquence of the word Especially since it captured different categories of audiences, notably the readership. In this research, we wanted to highlight this art by comparing the caricature of the accompanying text (the message of linguistics), in order to benefit the recipient and to exploit the caricature in life in the service of its different aspects (education, advertising, tourism, etc.)
Keywords: الكاريكاتير،الصورة الكاريكاتورية